Metabolism, structure and function of plant tetrapyrroles : control mechanisms of chlorophyll biosynthesis and analysis of chlorophyll-binding proteins - Grimm, Bernhard (Advances in botanical research, 2019)
Metabolism, Structure and Function of Plant Tetrapyrroles, Volume 91, the latest release in the Advances in Botanical Research series is a compilation of the current state-of-the-art on the topic. Chapters in this new release cover Tetrapyrrole Pigments of Photosynthetic Antennae and Reaction Centers of Higher Plants: Biochemistry, Biophysics, Functions, Molecular Mechanism of Antenna Regulation, Applications, Chlorophyll c: Synthesis, Occurrence, Light-Harvesting, Absorbance, Excitation Properties, Pigment Organization in Chlorophyll-Binding Proteins (FCP), Chlorophyll d and f: Synthesis, Occurrence, Light-harvesting, Absorbance, Excitation Properties, Pigment Organization in Chlorophyll-Binding Protein Complexes, Analysis of Chlorophyll, Precursors and Derivatives by New High-Performance Liquid Chromatography and Mass Spectrometry, and much more. Key Features: Presents the latest release in the Advances in Botanical Research series; Provides an Ideal resource for post-graduates and researchers in the plant sciences, including botany, plant biochemistry, plant pathology and plant physiology; Contains contributions from internationally recognized authorities in their respective fields. Readership: Postgraduates and researchers in plant sciences, including botany, plant biochemistry, plant physiology, plant pathology, virology, entomology, and molecular biology. --